Downregulation of 14‐3‐3β and 14‐3‐3ζ in lesions of psoriasis vulgaris. (21st March 2013) - Man, X.; Zhang, X.; Tang, J.; Chen, Y.; Li, H.; Xu, B.; Pan, L.
Summary Background The 14‐3‐3 proteins are a family of conserved regulatory molecules expressed in all eukaryotic cells, which play essential roles in a wide range of vital regulatory processes, including differentiation, proliferation and transformation. In mammalian cells, seven 14‐3‐3 isoforms (β, γ, ε, η, θ/τ, σ and ζ) have been identified, and each of these seems to have distinct tissue localizations and isoform‐specific functions. 14‐3‐3β and 14‐3‐3ζ are two important members of the 14‐3‐3 family. Aim To explore the role of 14‐3‐3β and 14‐3‐3ζ in normal skin and psoriasis vulgaris (PV) skin. Methods Using immunohistochemistry and western blotting, we measured expression of 14‐3‐3β and 14‐3‐3ζ in 30 PV lesions and 15 normal skin samples. The average optical density (OD) of immunostaining and the relative grey scale of immunoblotting for 4‐3‐3β and 14‐3‐3ζ were analysed by the t‐test. Results The average OD of immunostaining for 14‐3‐3β and 14‐3‐3ζ was 0.17 ± 0.00 and 0.24 ± 0.01, respectively, in psoriatic lesions, which was significantly lower than in normal controls (0.22 ± 0.01 and 0.37 ± 0.02, respectively; P < 0.01 for both). There was also a significant difference in the relative grey scale of 14‐3‐3β and 14‐3‐3ζ (0.52 ± 0.03 and 1.44 ± 0.06, respectively) in psoriatic lesions compared with normal control tissue (3.32 ± 0.15 and 2.76 ± 0.11, respectively; P < 0.01 for both). Conclusions Expression of 14‐3‐3β and 14‐3‐3ζ were lower in psoriatic lesions than in normal human skin tissue. We speculate that 14‐3‐3β and 14‐3‐3ζ may be involved in the regulation of normal skin function, thus decreased expression of 14‐3‐3β and 14‐3‐3ζ might precipitate the disturbance in proliferation and differentiation of keratinocytes seen in psoriasis.